Case of idiopathic isolated unilateral hypoglossal nerve palsy with spontaneous recovery - Gurung, Binay (BMJ Case Rep, 2018)
Isolated hypoglossal nerve palsy is uncommon because of its intimate relationship with the other lower cranial nerves. Keane reported that tumours, predominantly malignant, were the most common cause of hypoglossal nerve palsy. We report a case of isolated idiopathic unilateral hypoglossal nerve palsy in a 45-year-old Caucasian male where no cause could be identified despite extensive investigations. There was uncertainty around prognosis at onset due to the rarity of this condition. In the absence of a cause, an early referral to the speech and language therapist was made and interestingly our patient made an almost complete recovery within 18 months of onset. In a small case series, it has been reported that though rare, idiopathic hypoglossal nerve palsy has an excellent outcome in most cases, similar to the more common idiopathic seventh cranial nerve palsy (Bell’s Palsy).We recommend an early referral for physiotherapy in such cases.